A validation study of a consecutive interpreting test using many-facet Rasch analysis - Zhao, Nan (Frontiers in Communication, 2023)
Through many-facet Rasch analysis of a consecutive interpreting test, this paper validates the result of the test from four aspects: rating scale, raters, examinees and interpreting tasks. The study also identifies elements that affect the test results through bias analysis. The results of this analysis show that: 1) this rating scale and task design can effectively reflect the examinees’ interpreting competence, thus making it suitable for validating interpreting assessments; 2) one of the sub-scales: interpreting skills and manners, has a slightly negative effect on the overall validity of the assessment, making further revision on this sub-scale desirable.